PENGEMBANGAN KONTEN MEDIA INSTAGRAM PADA MATERI ANALISIS KUALITATIF KATION GOLONGAN IV DAN V - Safitri, Frisca Nadya; Widarti, Hayuni Retno; Utomo, Yudhi (Jurnal Visi Ilmu Pendidikan, 2025)
The Analytical Chemistry Fundamentals course, particularly the qualitative analysis content involving group IV and V cations which are abstract and conceptual, creates challenges for students in comprehending the instructed material. Several measures have been implemented to address these challenges, and one of them involves creating Instagram media content.. This study aims 1) develop Instagram media content related to qualitative analysis material of group IV and V cations, and 2) describe the level of feasibility   Instagram media content on the material. This research and development uses the RD method with   4D development model by Thiagarajan. The outcomes of this research manifest as Instagram media content covering the qualitative analysis of group IV and V cations, deemed suitable for utilization.This feasibility level is shown in the results of media validation of 92,29%, material validation of 93,63%, and readability trials of students in the five semester of the Department of Chemistry, State University of Malang by 93,46%.